THE EFFECT OF PROFITABILITY, PROFIT MANAGEMENT, AND FINANCIAL DISTRESS ON TAX AGGRESSIVENESS (STUDY ON COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE, 2016-2019) - Ayem, Sri; Chandra Putry, Nur Anita; Mahala Kelen, Gaudensia Hilaria (Perpustakaan dan Penerbitan Unismuh Makassar, 2020)
This research aims to examine the effect of profitability, earnings management, and financial distress on tax aggressiveness. The researcher used the secondary data, with the purposing sampling method as a sampling technique to the companies listed on the Indonesia Stock Exchange in the year 2016 up to 2019. There were 15 companies used as the data during four years, and there were 60 samples. Multiple regression analysis is used as the method of data analysis. The result of this research indicated that the effect of profitability, earnings management, and financial distress had a positive effect on tax aggressiveness.